Desain Internet of Things Untuk Perencanaan Produksi Pada Sektor Usaha Kecil Dan Menengah - Sulindawaty, S; Barus, Ravindra Jain; Pratama, Muhammad Dani (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Production is the most important part of the industrial world. Production planning is influenced by the number of products to be produced, production facilities, and delivery/ distribution of products by the company concerned in the coming period. Production planning greatly affects the survival of the company. In the industrial era 4.0, business competition has a real impact on small and medium enterprises (SMEs). Determining the amount of production in a directed and real-time manner has become a demand so that SMEs can survive in the industrial era 4.0. SMEs must be able to compete in the Internet of Things environment. To meet the demands of the industrial era 4.0 for small and medium enterprises, this research was conducted to produce an idea/thought framework in the form of Internet of Things design for production planning in the small and medium business sector.